A novel SWCNT-polyoxometalate nanohybrid material as an electrode for electrochemical supercapacitors. Issue 17 (13th April 2015) - Chen, Han-Yi; Al-Oweini, Rami; Friedl, Jochen; Lee, Ching Yi; Li, Linlin; Kortz, Ulrich; Stimming, Ulrich; Srinivasan, Madhavi
Abstract : A novel nanohybrid material that combines SWCNTs with a polyoxometalate (TBA)5 [PV2 Mo10 O40 ] (TBA-PV 2 Mo 10, TBA: [(CH3 (CH2 )3 )4 N] + ) is investigated for the first time as an electrode material for supercapacitors in this work. Abstract : A novel nanohybrid material that combines single-walled carbon nanotubes (SWCNTs) with a polyoxometalate (TBA)5 [PVV2MoVI10O40 ] (TBA-PV 2 Mo 10, TBA: [(CH3 (CH2 )3 )4 N] +, tetra- n -butyl ammonium) is investigated for the first time as an electrode material for supercapacitors (SCs) in this study. TheSWCNT-TBA-PV 2 Mo 10 material has been prepared by a simple solution method which electrostatically attaches anionic [PV2 Mo10 O40 ] 5− anions with organic TBA cations on the SWCNTs. The electrochemical performance of SWCNT-TBA-PV2 Mo10 electrodes is studied in an acidic aqueous electrolyte (1 M H2 SO4 ) by galvanostatic charge/discharge and cyclic voltammetry. In thisSWCNT-TBA-PV 2 Mo 10 nanohybrid material, TBA-PV 2 Mo 10 provides redox activity while benefiting from the high electrical conductivity and high double-layer capacitance of the SWCNTs that improve both energy and power density. An assembledSWCNT-TBA-PV 2 Mo 10 symmetric SC exhibits a 39% higher specific capacitance as compared to a symmetric SC employing only SWCNTs as electrode materials. Furthermore, theSWCNT-TBA-PV 2 Mo 10 SC exhibits excellent cycling stability, retaining 95% of its specific capacitance after 6500 cycles.